FcγR engagement reprograms neutrophils into antigen cross-presenting cells that elicit acquired anti-tumor immunity - Vijayashree Mysore (Nature Portfolio, 2021)
Neutrophils are versatile immune cells that may also serve as antigen-presenting cells (APC). Here the authors show that engaging FcγRs on neutrophils with immune complexes or an anti-FcγR-antigen conjugate induces neutrophil APC with comparable functions as classical dendritic cells, and with therapeutic potentials for cancer and infectious diseases.